Kepastian Hukum Akad Mudharabah pada Koperasi Al Fath Idaroh Kemakmuran Masjid Indonesia Tangerang Selatan - Prastowo Sidhi; Sirajuddin Sailellah; Zulkarnein Z (Postgraduate of Jayabaya University, 2019)
Implementation of the principle of legal certainty of mudharabah contract at Cooperative of Al FATH Idaroh Mosque Commonwealth of South Tangerang in its implementation based on Al-Quran, Al-Hadith, opinion of Gustav Radbruch, opinion of Muslim scientist, Act concerning Cooperatives, Act concerning Sharia Bangking, Ministerial Regulation of Small and Medium Enterprises on the Implementation of Savings and Loans and Sharia Financing Activities, the latest through the Regulation of the Minister of Cooperatives and SME Number 11/PER/M.KUKM/XII/2017 on the Implementation of Business Activities Savings and Loans and Sharia Financing, and Fatwa DSN of MUI No: 07/DSN-MUI/IV/2000 concerning Mudharabah Financing (Qiradh). The method used in this research is normative legal research. The data used are secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. From the research results, can be concluded that the has materialized legal certainty of mudharabah contract at Al Fath Cooperative Idaroh Commonwealth Mosque Indonesia South Tangerang has been achieved. The obstacles in applying the legal certainty principle of mudharabah agreement at Al Fath Cooperative Idaroh Commonwealth Mosque Indonesia South Tangerang referring to Lawrence M. Friedman's Law System Legal Theory and John Rawls’s Justice Law Theory. There should be a Law on BMT and socialization so that people understand BMT.